PENGUKURAN WAKTU KERJA KARYAWAN BENGKEL TOYOTA PT. DUNIA BARUSA DI KOTA BANDA ACEH - Muzakir Muzakir; Heri Tri Irawan; Iing Pamungkas (Jurnal Optimalisasi, 2018)
The study aims to analyze the level of employee performance in the process of changing car oil in the workshop of PT. Barusa world. The study was conducted on operators who work in the car oil change section using the time study method. The study was conducted in several stages, namely preliminary observations and then followed by determining the number of observations, collecting data, conducting data processing, analyzing the results of data processing and finally concluding the results of research. The final result obtained in this study is the standard time needed to complete the process of changing car oil is 14.61 minutes with the number of operators as much as 2 people.